The Total Phenolic Fraction of Anemarrhena asphodeloides Inhibits Inflammation and Reduces Insulin Resistance in Adipocytes via Regulation of AMP-Kinase Activity - Zhao, Wenjun; Wang, Meng; Shao, Lu; Liao, Min; Liu, Kang; Huang, Fang; Liu, Baolin (Planta Medica, 2014)
Anemarrhena asphodeloides is widely used for treatment of metabolic disorders in traditional Chinese medicine. This study investigated the effects of the total phenolic fraction of Anemarrhena asphodeloides on regulation of insulin sensitivity in adipocytes. Through treatment with macrophage-derived conditioned medium, insulin resistance was induced in adipocytes with IKKβ activation and dysregulation of adipokine production. However, these changes were reversed by treatment with the total phenolic fraction of A. asphodeloides (1, 10, 50 µg/mL). It regulated serine/tyrosine phosphorylation of insulin receptor substrate-1 and subsequently restored Akt phosphorylation in response to insulin, thereby leading to the improvement of insulin-mediated glucose uptake. The total phenolic fraction of A. asphodeloides enhanced AMP-activated protein kinase phosphorylation, and this action contributed to the inhibition of inflammation implicated in insulin resistance. In conclusion, the total phenolic fraction of A. asphodeloides attenuated insulin resistance in adipocytes by inhibition of inflammation in an AMP-activated protein kinase-dependent manner.
Keywords: Anemarrhena asphodeloides; Asparagaceae; adipocytes; inflammation; insulin resistance; AMP-kinase